PENGARUH KUALITAS PRODUK, HARGA DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN MOBIL TOYOTA CALYA DI NASMOCO SLAMET RIYADI SURAKARTA - Thoriq Amri Yahya; Burhanuddin Burhanuddin; Rochmi Widayanti (ITB AAS INDONESIA Surakarta, 2019)
This study was conducted to determine how much the influence of the independent variables consisting of product quality, price and brand image on the purchase decision of the Toyota Calya car in Nasmoco slamet Riyadi Surakarta. The sample in this study was 78 respondents taken from the consumer population who bought a Toyota Calya car at Nasmoco Slamet Riyadi in the period 2017-2018. The technique used is purposive sampling. As in general quantitative research, this research uses t-test analysis techniques for hypothesis testing, F test and multiple linear regression analysis. The results of the f test produce Fcalculate = 35,644 indicating that the variable of product quality, price and brand image jointly influence the purchasing decision of the Toyota Calya car at Nasmoco Slamet Riyadi. The results of the t test show the most dominant price variable influencing the dependent variable (Y) with a value of t calculate = 2.688 Keywords : product quality, price, brand image, purchasing decisions